Students’ Perceptions of the Use of English as a Medium of Instruction in a Fifth-Grade Classroom - Athaya Ithhar Ul Haq; Harwintha Yuhria Anjarningsih (Universitas Al Azhar Indonesia, 2026)
This study focuses on students’ perceptions of English as a Medium of Instruction (EMI) in a fifth-grade classroom. This research applies a qualitative case study design involving 28 fifth-grade students from a Cambridge curriculum school who had direct experience with EMI in their daily learning activities. Data were collected by semi-structured focus group interviews and analysed using thematic analysis. The findings suggest that most students view EMI positively because of their familiarity and exposure to English, but these perceptions are not always stable, as some students still experience difficulties when dealing with unfamiliar vocabulary or complex tasks. The study reveals that students’ perceptions are not limited to positive and negative categories, but also include conditional responses, where perceptions depend on subject matter, classroom activities, and emotional conditions. The findings also identified several factors, including vocabulary mastery, classroom interaction, teacher-related factors, emotional conditions, and language exposure. This study contributes to existing EMI research by showing that elementary students’ perceptions are not limited to positive and negative categories, but may also be conditional and context dependent.Keywords - Elementary School, English as a Medium of Instruction, Student’s Perceptions.